2015
DOI: 10.1080/15226514.2015.1109607
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of lead-contaminated soil bySinapis arvensisandRapistrum rugosum

Abstract: Nowadays, public concern relating to ecological deleterious effects of heavy metals is on the rise. To evaluate the potential of Rapistrum rugosum and Sinapis arvensis in lead- contaminate phytoremediate, a pot culture experiment was conducted. The pots were filled by soil treated with different rates of leadoxide (PbO) including 0 (control), 100, 200, 300, 400, and 500 mg Pb per 1 kg soil. Germinated seeds were sown. Surprisingly, with increasing concentration of Pb, dry weight of R. rugosum and S. arvensis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Immobilization of anionic heavy metals (As and Cr) were greater in acidic soils, while retention of cationic heavy metals (Pb, Cd and Zn) were found to be higher in calcareous soil. Immobilization of Pb, As and Cr increased more than 82% through application of 10% of nZVI; however, nZVI could not significantly affect immobilization of Cd (only 13% to 42%), regardless of the soil pH [16,17].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Immobilization of anionic heavy metals (As and Cr) were greater in acidic soils, while retention of cationic heavy metals (Pb, Cd and Zn) were found to be higher in calcareous soil. Immobilization of Pb, As and Cr increased more than 82% through application of 10% of nZVI; however, nZVI could not significantly affect immobilization of Cd (only 13% to 42%), regardless of the soil pH [16,17].…”
Section: Introductionmentioning
confidence: 86%
“…1.5 g/kg Pb in plant tissue after four months [15]. In a study by Saghi et al [16], 100 to 500 mg/kg Pb were applied to soil, and it was found that growth parameters of R. rugosum and S. arvensis did not decrease significantly. In addition, higher accumulation of Pb in roots of the studied plant species was observed compared to shoots.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations